Barriers to Learning Faced by Students Who are Deaf and Hard of Hearing in Higher Education Institutions in Tanzania - Kisanga, Sarah Ezekiel (Papers in Education and Development, 2020)
This qualitative study explored the barriers to learning faced by students who are deaf and hard of hearing using ten students who are deaf and hard of hearing in higher education. Thematic analysis revealed shortages and questionable quality of the hearing aids, inadequacy of sign language interpreters and unsupportive classrooms as resource barriers limiting effective learning. The study further uncovered overreliance on oral dominated lectures, difficulties in speech reading and lecturers ' reluctance to provide lecture notes as pedagogical barriers. Based on these findings, the study recommends teacher education curriculum to incorporate a special course on teaching pedagogies that address diverse needs of students who are deaf in inclusive education settings. Keywords: communication barrier, deaf, hard of hearing, inclusive education